THE IMPLEMENTATION OF TAHFIDZ QUR’AN PROGRAM AT MTS HIFZHIL QURAN ISLAMIC CENTER NORTH SUMATERA - Siti Halimah; Muhammad Dalimunthe; Ummi Kalsum Nsution (State Islamic University of North Sumatra Indonesia, 2020)
The purpose of this study is to describe: 1) Planning the Tahfidz Qur’an at Madrasah Tsanawiyah Hifzhil Quran Foundation Islamic Center Foundation in North Sumatra; 2) Organizing the Tahfidz Qur’an at Madrasah Tsanawiyah Hifzhil Quran Foundation Islamic Center Foundation in North Sumatra; 3) Implementation of the Tahfidz Al-Qurandi Madrasah Tsanawiyah Hifzhil Quran Foundation Islamic Center Foundation in North Sumatra; 4) Supervision of the Tahfidz Qur’an at Madrasah Tsanawiyah Hifzhil Quran Foundation Islamic Center Foundation in North Sumatra; and 5) Factors supporting and inhibiting the implementation of the Tahfidz Qur’an at Madrasah Tsanawiyah Hifzhil Quran Foundation Islamic Center Foundation in North Sumatra. This research uses a qualitative approach with descriptive methods. Data collection uses interview, observation, and document study techniques. To guarantee the validity of the data of the findings and the authenticity of the research refers to the use of data validity standards consisting of credibility, transferability, dependability, and confirmability. This study found that: 1) Planning the tahfidzul quran program at Tsanawiyah Islamic Center in North Sumatra, Islamic Center was carried out by consensus by involving all elements of the education provider; 2) Organizing the tahfidzul quran program carried out by making regular roster or schedule, allocating teachers, and providing learning facilities; 3) The implementation of Qur’an tahfidzh program is quite good. Related to the use of the method of implementing tahfidz; 4) Supervision of program implementation is the headmaster of the madrasa and the teachers appointed to manage the program; and 5) Supporting factors for the successful implementation of this program are due to the strong and high motivation to learn from students to memorize. Keywords: Planning, Organizing, Implementation, Supervision